Електрохімічне одержання оксиду вольфраму з псевдосплаву карбідного типу WC–Co - Тульський, Геннадій Георгійович; Ляшок, Лариса Василівна; Османова, Марина Павлівна; Соболева, Аліна Едуардівна (Інститут газу НАН України, 2019)
Widespread use of specialized tools, the component part of which is tungsten, leads to the accumulation of its secondary raw materials (worked tools, cutters, drills, etc.). That is why there is a need to create technologies for recycling of the demanded metals, in particular tungsten. The purpose of this work is to study the anode behavior of carbide pseudoalloy type WC-Co in solutions of nitric acid with the addition of fluoride acid to obtain, as a target product, higher tungsten oxide in one stage. The corrosion behavior of carbide type pseudoalloy in acid solutions has been studied, and it has been found that the highest oxidation rate occurs in a concentrated solution of nitric acid. In order to accelerate the process and to increase the yield on the substance, adding to the fluoride acid working electrolyte has been proposed. As a result of the researches, it has been found that the behavior of the dissolution of pseudoalloys of the carbide type is characterized by the properties of the main component — tungsten. An electrolyte for obtaining higher tungsten oxide in one stage has been proposed.
Electro-Chemical Production of Tungsten Oxide from Pseudo-Alloy Carbide Type WC–Co
Keywords: tungsten oxide; WC-Co alloy; nitric acid; anode dissolution; oxidation